Les trois phénomènes de la mutation des biens meubles en biens immeubles - Goulet, Jean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
On September 30th, 1977, the Supreme Court of Canada has delivered a judgment in the case of Cablevision (Montreal) Inc. v. Le Sous-ministre du Revenu de la province de Québec, where the fundamental problem of the qualification of things has once more been reviewed. In this instance, the Court had to qualify a network of wires and various apparatus belonging to the appellant and fixed, under a lease, by this corporation to poles being the property of the Bell Telephone Co. and the Hydro-Québec Corporation, as well as an antenna, also belonging to Cablevision, fixed to the roof of the Montreal skyscraper Place Ville-Marie, the property again of a third party. All these things, formerly moveables, have been held by the Supreme Court to have become immoveable by nature, due to their close attachment to the buildings to which they were affixed. This judgment will have to be distinguished from the former leading case of Nadeau v. Rousseau which held that the incorporated moveable had to become part of the building itself or be indispensable to its natural use. Since a TV antenna fixed to a building is not an essential part ofthat building nor even useful to it, the Court must fall back on the test of close attachment in order to determine its character. The writer of this paper feels this decision is sound reasoning, and recalls the true nature and origins of property immoveable by its nature. Since only land is a real immoveable by nature, buildings are held so only because of their attachment to the land. Again, things immoveable by their destination are held to be so mainly because of their close relationship to the building. The test of physical attachment is then the only true objective test to qualify moveable things when affixed to an immoveable.